INNOVATION AND REPUTATIONAL SUSTAINABILITY OF BUSINESS IN A MARTYR STATE - BOKOVETS, Viktoriia; KHYMYCH, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the key role of innovation in ensuring the sustainability and adaptability of modern entrepreneurship under martial law in Ukraine. It is emphasized that the full-scale war has created unprecedented challenges for business, including the destruction of infrastructure, a decrease in the purchasing power of the population, the complication of logistics, the loss of personnel, and a high level of uncertainty. Under such conditions, it is innovation that acts not only as a tool for modernization, but also as a means of ensuring the survival of enterprises and their further development. The main areas of innovation activity of Ukrainian companies during the crisis period are analyzed, including: digitalization of business processes, relocation of production, reorientation to exports, adaptation of business models, and creation of new products that meet the current needs of society. Special attention is paid to the issue of forming a positive image of enterprises, which becomes especially important during the war. It is emphasized that social responsibility, transparent communication and patriotic position of companies play a crucial role in maintaining trust from consumers, partners and investors. The concept of reputational stability as a new type of intangible asset that ensures strategic business stability in the face of external threats is considered. Promising directions for further research in the field of innovative entrepreneurship in the context of war and post-war recovery are identified. An integrated approach to the development of innovation and the image of enterprises will not only contribute to their survival in wartime, but will also create the foundation for successful post-war reconstruction and sustainable economic growth of Ukraine. It is the implementation of scientifically based strategies in this area that will be of great importance for strengthening the national economy and increasing its competitiveness in the global market.
Keywords: innovation; reputation; business; innovative development; reputational stability; crisis